CTAB Enhances Chemo-Sensitivity Through Activation of AMPK Signaling Cascades in Breast Cancer - Pan, Yue; Zhang, Yunqiu; Chen, Qing; Tao, Xufeng; Liu, Jianzhou; Xiao, Gary Guishan (Frontiers in Pharmacology, 2019)
Metabolic reprogramming is thought to be one of the initiators in cancer drug resistance. It has been shown that CTAB is capable of interfering the efficiency of cancer therapy by regulation of cell metabolic reprogramming. In this study, we hypothesized that AMPK as a key metabolic regulator plays a crucial role in regulation of breast cancer drug resistance, which could be alleviated by treatment of CTAB. We observed that CTAB can improve the DOX sensitivity of the breast cancer cells by inhibition of the ATP-dependent drug-efflux pump P-gp complex through activation of the AMPK-HIF-1α-P-gp cascades. The CTAB effect was also confirmed in vivo showing low systemic toxicity. Taken together, our results showed that CTAB sensitized drug resistance of breast cancer to DOX chemotherapy by activating AMPK signaling cascades both in vitro and in vivo, suggested that CTAB may be developed as a promising and novel chemosensitizer and chemotherapeutic candidate for breast cancer treatment.